Assessment of Reliability of YouTube Videos on Orthodontics - Delal Dara Kılınç; Gülşilay Sayar (Galenos Yayinevi, 2019)
Objective: In addition to being an entertainment channel, YouTube is also one of the most popular visual information sources today. People search YouTube to consult also on orthodontics, as well as on many other topics. The objective of the present study was to analyze the quality and reliability of information of the videos on YouTube about orthodontics.Methods:YouTube was searched systematically by two researchers on orthodontics by using the keywords "Orthodontics," "Orthodontist," and "Orthodontic Treatment." Videos on the first three pages (60 videos) for each keyword were assessed. Researchers evaluated the reliability of the videos by using the Reliability Score (adapted from DISCERN) and the quality of the videos by using the Global Quality Score (GQS).Results:The mean GQS results were 2.6±1.3 for videos in the "Orthodontist" group, 3.2±1.3 for videos in the "Orthodontics" group, and 2.3±1.2 for videos in the "Orthodontic Treatment" group on a 5-point scale. The Reliability Score results were 2, 2, and 1.5 for videos in the "Orthodontist," "Orthodontics," and "Orthodontic Treatment" groups, respectively, on a 5-point scale. The Intraclass Correlation Coefficient results presented a positive relationship between the researchers.Conclusion:Owing to the lack of peer-review process and pre-upload scientific evaluation process, videos on YouTube can lead the public to misinformation.